Slave Counterpoint : Black Culture in the Eighteenth-Century Chesapeake and Lowcountry - Morgan, Philip D., 1949- (Book collections on Project MUSE., 1998)
"Morgan explores the role of land and labor in shaping culture, the everyday contacts of masters and slaves that defined the possibilities and limitations of cultural exchange, and finally the interior life of Blacks--their social relations, their family and kin ties, and the major symbolic dimensions of life: language, play, and religion. He provides a balanced appreciation for the oppressiveness of bondage and for the ability of slaves to shape their lives, showing that, whatever the constraints, slaves contributed to the making of their history. Victims of a brutal, dehumanizing system, slaves nonetheless strove to create order to their lives, to preserve their humanity, to achieve dignity, and to sustain dreams of a better future."--The publisher